Pemberdayaan Masyarakat Desa Bokasape Timur melalui Program Kesehatan Edukasi Pencegahan Virus African Swine Fever - Ndjandji, Andrianto Umbu (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Fever virus that can affect wild and farmed pigs. This virus can sicken or kill 100% of the population if attacked. This ASF virus is not dangerous or contagious to humans, and in an in vitro environment, the resistance of ASF viruses to exotic diseases is very high. Irresponsible development of the problem can be a serious problem in the East Bokasape Village epidemic ASF control program. The population's ignorance and lack of correct information about the ASF virus epidemic has a significant social impact. Prevention can be done by implementing various activities, one of which is counseling/education and leadership activities, assuming that it can provide information and scientific knowledge about ASF outbreaks to all levels of society. The method used is to provide public education and advocacy. Duties and responsibilities of the Community Service Team include supervision/training of pigs and preventive supervision and direct monitoring according to PRISMA recommendations for husbandry, measures to strengthen biosecurity and continuous surveillance.